2021
DOI: 10.1021/acsanm.1c00278
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Nanomaterials for Microwave Absorption and Electromagnetic Interference Shielding: A Review

Abstract: Core–shell nanoparticles are a unique class of nanostructured materials, which received significant attention in the last two decades owing to their exciting properties and a wide variety of applications. By judiciously tuning the “core” as well as the “shell”, an assortment of “core–shell” nanostructures can be obtained with tailorable properties which can play pivotal roles in designing materials for electromagnetic interference (EMI) shielding and microwave absorption. In recent times when the use of high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(61 citation statements)
references
References 169 publications
0
61
0
Order By: Relevance
“…The yolk-shell structure, a special type of core-shell structure, features interstitial void space, modifiable inner cores, high specific surface area, as well as low density, owing to its distinct core@void@shell configuration. [106] In 2015, Che et al systematically compared the response mechanism of CoNi@ SiO 2 @TiO 2 core-shell and CoNi@air@TiO 2 yolk-shell microspheres, and demonstrated that yolk-shell structure helped to minimize the impedance gap to ensure the penetration of incident microwave. [6a] Wang et al employed an in situ reduction approach to construct Fe 3 O 4 @C yolk-shell nanocomposites.…”
Section: D Core-shell Structuresmentioning
confidence: 99%
“…The yolk-shell structure, a special type of core-shell structure, features interstitial void space, modifiable inner cores, high specific surface area, as well as low density, owing to its distinct core@void@shell configuration. [106] In 2015, Che et al systematically compared the response mechanism of CoNi@ SiO 2 @TiO 2 core-shell and CoNi@air@TiO 2 yolk-shell microspheres, and demonstrated that yolk-shell structure helped to minimize the impedance gap to ensure the penetration of incident microwave. [6a] Wang et al employed an in situ reduction approach to construct Fe 3 O 4 @C yolk-shell nanocomposites.…”
Section: D Core-shell Structuresmentioning
confidence: 99%
“…Though plentiful excellent reviews have been reported to introduce the advances of EM wave absorbing materials, [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ] they mainly focus on introducing EM wave loss materials on basis of material categories, such as carbon materials, [ 43 , 44 , 45 , 46 , 47 , 48 ] MOFs deprived materials, [ 49 , 50 , 51 ] boron nitride, [ 52 ] conducting polymers, [ 53 , 54 ] ferrites, [ 55 , 56 , 57 ] sulfides, [ 58 ] and MXene [ 59 , 60 , 61 ] or design of peculiar micro/nanostructure. [ 62 ] As far as we know, the topic that lies on EM wave loss mechanisms and models has been rarely reported. Herein, this review provides a comprehensive summary on dielectric mechanism study in EM wave absorption field for the purpose of supplying guidance for novel EM wave absorbers design through mechanism perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Though plentiful excellent reviews have been reported to introduce the advances of EM wave absorbing materials, [ 43–66 ] they mainly focus on introducing EM wave loss materials on basis of material categories, such as carbon materials, [ 43–48 ] MOFs deprived materials, [ 49–51 ] boron nitride, [ 52 ] conducting polymers, [ 53,54 ] ferrites, [ 55–57 ] sulfides, [ 58 ] and MXene [ 59–61 ] or design of peculiar micro/nanostructure. [ 62 ] As far as we know, the topic that lies on EM wave loss mechanisms and models has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Yolk–shell structure is a special kind of core–shell structure and the structure can also be called a core@void@shell structure, which means that there is not direct contact between the core and the shell. The existence of void provides unique advantages such as low density and large surface area [ 17 , 18 , 19 ]. Furthermore, the outside dielectric shell (SnO 2 [ 20 ], MnO 2 [ 21 ], carbon [ 22 ]) cannot only effectively protect naked magnetic core from oxidation, but also provide dielectric loss capacity.…”
Section: Introductionmentioning
confidence: 99%